Risk of adverse pregnancy outcomes stratified for pre-pregnancy body mass index. (2nd July 2016) - Wei, Yu-Mei; Yang, Hui-Xia; Zhu, Wei-Wei; Liu, Xin-Yue; Meng, Wen-Ying; Wang, Yong-Qing; Shang, Li-Xin; Cai, Zhen-Yu; Ji, Li-Ping; Wang, Yun-Feng; Sun, Ying; Liu, Jia-Xiu; et al.
Abstract: Objective : To estimate the risk of adverse maternal and perinatal outcomes in women with different pre-pregnancy body mass index (BMI). Methods : We conducted a cohort study with 14 451 singleton pregnancies in 15 medical centers in Beijing between 20 June 2013 and 30 November 2013 using cluster random sampling. We divided participants into four groups based on pre-pregnancy BMI: Group A (underweight): BMI < 18.5 kg/m 2, Group B (normal): 18.5–23.9 kg/m 2, Group C (overweight): 24–27.9 kg/m 2, Group D (obesity): ≥28 kg/m 2 . We used multivariate analysis to evaluate the association of the risk of adverse pregnancy outcomes and pre-pregnancy BMI. Results : The prevalence of maternal overweight and obesity was 14.82% (2142/14 451) and 4.71% (680/14 451) in the study population, respectively. Higher pre-pregnancy BMI is associated with higher prevalence of gestational diabetes (GDM), macrosomia, Cesarean section (C-section), preeclampsia and postpartum hemorrhage. Pre-pregnancy overweight or obesity increases the risk of adverse pregnancy outcomes, regardless of GDM status. Conclusions : Pre-pregnancy overweight or obesity is associated with increased risk of adverse pregnancy outcomes. Nutrition counseling is recommended before pregnancy in women who have overweight or obesity.